The effects of yellow pumpkin (Cucurbita moschata) substitution on stick acceptance - Silvia Nanda; Erwandi Erwandi (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
Sticks refer to snacks or cakes made of wheat flour, tapioca or sago flour, fat, eggs, and water. Sticks have a long flat shape processed with fried techniques, a savory taste, and a crisp texture. Sticks are made of raw materials and additional ingredients. The raw material is flour and is sometimes substituted by pumpkin flour. Pumpkin stick is alternative food to increase the production of pumpkin flour. This study aimed to determine the effects of using 10%, 20%, and 30% pumpkin flour on organoleptic properties (colors, smells, tastes, and textures) of sticks. This study employed an experimental design with a non-factorial completely randomized design (RAL) with three treatments and three repetitions. Moreover, 15 untrained panelists from Dayah Panjoe Village, Kuta Blang District, Bireuen Regency were involved to test the treatments. This study found that the highest nutritional value of the stick color was 3.64 (moderately liked by the panelists). The highest value of stick smell was 3.62 (moderately liked by the panelists). Meanwhile, the highest value of stick taste was 4.13 (liked by the panelists). Finally, the highest value of stick texture was 3.40 (moderately liked by the panelists). This research concluded that the substitution of 10%, 20%, and 30% pumpkin flour significantly affected organoleptic properties, such as color, smell, taste, and texture. This research suggests that further research measures the temperature of the frying pan and preferably greases the pumpkin flour with mashing.